Drug Benefits and Risks International Textbook of Clinical Pharmacology : Revised 2nd edition - Boxtel, Chris J. Van (IOS Press, 2013)
The subject of both sections of this chapter is complex. In the first place because after marketing the spectators in the therapeutic scene have a tendency to see different plays. Healthy people see something different from patients and the perspectives of governments, health insurers and manufacturers are all different. Furthermore we know that with respect to drug use important differences between countries exist and that intercultural and interethnic variations can have a decisive influence on the final outcome of drug use. It might therefore be good to first cite some figures to illustrate that in the modern world pharmaceuticals cannot and should not be considered as trivialities.